HUBUNGAN ANTARA KARIES DENGAN KEJADIAN STUNTING PADA ANAK DI SD BANJARMASIN - Ika Kusuma Wardani; Renie Kumala Dewi; Erika Norfitriah (Mitra Raflesia (Journal of Health Science), 2022)
Background: Dental caries makes children experience loss of chewing power and digestive disorders which result in less than optimal growth or stunting.Purpose: The purpose of this study was to determine the correlation between dental caries status and stunting among children in Mantuil 3 Elementary School Banjarmasin.Methods: This is a correlational study with a cross-sectional approach. Data collection was conducted in Februari 2022 and 40 children participated. The data analysis was performed to analyze for frequency distribution and the Spearman correlation test was used to measure the strength of the correlation between variables.Results: It was reported that most of the respondents who get stunting incidence, as many as 22 child (55%) were male. Most of the respondents experienced caries, as many as 30 child (75%). Based on the results of the Spearman correlation test, the value of Sig. 0.036 < 0.05 was obtained. Furthermore, the direction of the positive relationship can be seen from the sign of the coefficient correlation of 0.332, which means that the low relationship between caries and stunting.Conclusions: These results are expected to be the basic data for future research about caries and stunting. This can reduce the impact of the caries and stunting incidence. Keywords: Dental caries, Stunting, Child dental health, Caries status